Transformasi Budaya Organisasi melalui Internalisasi Core Values AKHLAK di PT TASPEN Kantor Cabang Jember - Rohman, Hermanto; Helpiastuti, Selfi Budi; Khasanah, Fitriatul (Contemporary Public Administration Review, 2024)
The Trusting, Competent, Harmony, Loyal, Adaptive, and Collaboarative (AKHLAK) Core Values serve as a unifying element for work culture, moral principles, and behavioral guidelines that must be implemented by human resources in state-owned enterprises, including TASPEN Jember. This is crucial for an organization’s progress due to recent challenges faced by state-owned enterprises, such as a lack of adherence to high moral standards. The objective of this research is to understand the changing process of organizational culture at TASPEN Jember through the implementation of AKHLAK Core Values. The theory used in this research is Kurt Lewin's (1947) Change of Model Theory. This study employs a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation. The data were then tested for validity and analyzed through source and technique  triangulation. The results of this study indicate the stages or processes of organizational culture transformation through the phases of unfreezing, movement, and refreezing. The transformation process begins with the unfreezing stage, which involves dissolving the old culture of Taspen, known as TASPENKU. During this phase, employees are motivated to adapt and open themselves to change. This is followed by the movement stage, where Core Values AKHLAK are implemented. In this phase, employees are required to apply every aspect of AKHLAK values within their work environment. Finally, the refreezing stage involves TASPEN Jember employees maintaining and reinforcing the AKHLAK values that have been successfully adopted.